Outsourcing Human Resource Functions and their Impact on Organizational Performance (Global Journal of Management and Business Research, 2020)
In today's rising competition, the benefit generated by the development of high organizational quality is becoming more important. The role of human resource tasks and the culture of organizations can impact the achievement of substantial organizational effectiveness, which in return draw much more attention from both theoreticians and practitioners. Outsourcing is deemed one of the tools which companies use to reinforce their core competencies to assign their resources effectively. The rise of globalization has transformed outsourcing into one of the broadly adopted business plans towards supplying exceptional services to consumers. As can be seen by the ever-increasing trends in outsourcing, the literature on how outsourcing activities affect manufacturing companies' results is insufficient. The main aim of this research was to investigate the impact on the performance of the outsourcing of human resources functions.
Keywords: outsourcing; human resources; organizational performance; performance